Hydrothermal Synthesis, Crystal Structure of Zinc(II) Complex of bis(2-Benzimidazole) and Aromatic Carboxylate Ligands - Feng, Guo-Dong; Jiang, Luan (Asian Journal of Chemistry, 2011)
A novel one-dimensional zinc(II) complex: [Zn2L2(H2C3PIm)2]n (1) with 2-carboxymethylbenzoic acid (H2L) and 2,2'-(1,3-propanediyl)bis(1H-benzimidazole) (H2C3PIm) has been synthesized by means of hydrothermal method and characterized by X-ray single-crystal diffraction. The crystal is of triclinic, space group P-1 with a = 1.3354(5) nm, b = 1.3991(5) nm, c = 1.4245(5) nm, a = 83.617(5)°, b = 70.742(5)°, g = 70.913(5)°, V = 2.3744(15) nm3, Dc = 1.451 g cm-3, Z = 2, F(000) = 1068, Goof = 1.073, R1 = 0.1067, wR2 = 0.3379. The complex 1 shows a novel one-dimensional (1D) zigzag chain structure along the a axis and further extended into a 2D supramolecular structure through N-H···O hydrogen bonding interactions. The p-p packing interactions contribute to the formation of the three-dimensional supramolecular architecture and stabilize the crystal structure.